Compensation, Organizational Loyalty, and Work Motivation as Determinants of Health Worker Performance in Cipayung Primary Health Centers, East Jakarta - Latifan, Sepri; Sudarman, Enjang; Kusuma Devi, Rr Nurwulan (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the effect of compensation, loyalty, and work motivation on the performance of healthcare workers at Cipayung Community Health Center, East Jakarta. The research employed a total sampling method with 38 respondents, and data analysis was conducted using correlation and regression tests with SPSS version 22. The results indicate that compensation has a significant effect on healthcare worker performance, with a t-value of 4.722 > t-table 1.980 and a regression equation of Y = 12.322 + 0.720X1. Loyalty also has a significant effect, with a t-value of 2.218 > t-table 1.980 and a regression equation of Y = 6.307 + 0.848X2. Work motivation significantly affects performance, with a t-value of 2.145 > t-table 1.980 and a regression equation of Y = 6.657 + 0.834X3. Simultaneously, compensation, loyalty, and work motivation significantly influence performance, as evidenced by an F-value of 85.436 > F-table 1.994. The Adjusted R Square value of 0.790 indicates that 79.0% of the variation in performance can be explained by these three variables, while the remaining 21.0% is influenced by other factors outside the model. The findings underscore the need for policies to enhance the welfare of healthcare workers through adequate compensation, strengthened loyalty, and increased work motivation to optimize performance and improve the quality of public health services.